(untitled) (East West Medical College Journal, 2025)
Acute stroke remains a medical emergency even during the COVID-19 pandemic. Most patients with COVID-19 infection present with constitutional and respiratory symptoms; while others present with atypical gastrointestinal, cardiovascular, or neurological manifestations. Here we are presenting a case of COVID-19 Pneumonia with Encephalitis in a 37 year old male, who presented initially with weakness of right side of the body & slurring of speech; with history of fever for 2 days 10 days back. Diagnosis was confirmed by RT-PCR for COVID 19, HRCT Chest & MRI of Brain. Antiviral medications along with steroid & anticonvulsant were started immediately after the diagnosis and the patient responded very well with subsidence of fever and feeling of wellbeing. EWMCJ Vol. 13, No. 2, July 2025: 159-163